Influence of hydrophilicity on adsorption of caffeine onto montmorillonite - Kenichiro Yamamoto; Takashi Shiono; Ryoto Yoshimura; Yasuto Matsui; Minoru Yoneda (Adsorption Science & Technology)
Some types of montmorillonite containing different interlayer ions were prepared and the changes in the interlayer spacings, the hydrophilicity, and the characteristics of adsorption of caffeine in solution were observed. Ion exchange treatments were performed using Li, Na, K, Rb, Cs, Mg, Ca, Sr, or Ba. As a result, Li- and Na-type montmorillonite showed larger interlayer distance (1.31–1.53 nm), than K, Rb, and Cs-type montmorillonite (1.23–1.26 nm). In the measurement of hydrophilicity using a pulse NMR-based particle interface analyzer, Li- and Na-type montmorillonite showed higher hydrophilicity. In addition, K Lang , which indicates the interaction with caffeine, was 0.25–0.32 l/mmol, which is lower than K-, Rb-, and Cs-type montmorillonite (1.14–1.60 l/mmol). It is possible that adsorption of water molecules inhibits caffeine from adsorbing. Because of the difficulty of exchange between caffeine and water molecules in interlayer of the Li- and Na-type montmorillonite, the interaction with caffeine decreased. Alternatively, another possibility is that when highly hydrophilic montmorillonite retains many water molecules, the caffeine adsorption sites are blocked by water molecules. In either case, hydrophilicity has a large influence on the adsorption of caffeine onto montmorillonite.